Mouth development of Malaysian river catfish, Mystus nemurus (C&V) larvae - El Hag, Ghada Ahmed; Kamarudin, Mohd Salleh; Saad, Che Roos; Daud, Siti Khalijah (Marsland Press, 2012)
Ontogenetic morphological development for the mouth of Malaysian river cat fish Mystus nemerus larvae from hatching to 21 days post-hatch (dph) was studied to facilitate and determine suitable food and food particle size for the growing larvae. The eggs began to hatch 2 days after fertilization (daf) and most of the larve hatched within 2-4 daf. The larval mouth opened at the end of the 1 dph and the commencement of external feeding began on 4 dph following the jaw movement. The barbels appeared on the upper jaw and lower jaw on 3 dph.Tow small barbels appeared around the olfactory pits by 5 dph. Free neuomasts were observed below the lower jaw on 7 dph and around the olfactory pits, eyes,and upper jaw operculum by 9 dph. Linear relationships between mouth size (at 45˚and 90˚ opening) and total length of fish were established.